2011
DOI: 10.1016/j.concog.2011.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Learning to use novel objects: A training study on the acquisition of novel action representations

Abstract: a b s t r a c tMany studies have suggested that the motor system is organized in a hierarchical fashion, around the prototypical end location associated with using objects. However, most studies supporting the hierarchical view have used well-known actions and objects that are highly over-learned. Accordingly, at present it is unclear if the hierarchical principle applies to learning the use of novel objects as well. In the present study we found that when learning to use a novel object subjects acquired an ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…Moreover, in line with studies stressing the role of object function in object learning (Träuble and Pauen 2007), it has been shown that the presence of salient action effects or an object's function affects the object representation acquired during the training process (van Elk et al 2011). Evidence for the role of first-hand action experiences comes from a study of van Elk et al (2011). In this study, two groups of subjects were trained to use novel objects.…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…Moreover, in line with studies stressing the role of object function in object learning (Träuble and Pauen 2007), it has been shown that the presence of salient action effects or an object's function affects the object representation acquired during the training process (van Elk et al 2011). Evidence for the role of first-hand action experiences comes from a study of van Elk et al (2011). In this study, two groups of subjects were trained to use novel objects.…”
Section: Introductionmentioning
confidence: 88%
“…Within each object set, one object could be brought toward the ear (ear-object) and the other toward the nose (nose-object). In the previous study (van Elk et al 2011), the ear-object produced a sound when brought toward the ear and the nose-object an odor. One of the ear objects should be grasped with a pronated powergrip and the other with a supinated powergrip to move it toward the ear.…”
Section: Stimulimentioning
confidence: 97%
See 3 more Smart Citations